Bioactive molecules and antioxidant activity in durum wheat grains and related millstream fractions. (14th August 2013) - Acquistucci, Rita; Melini, Valentina; Carbonaro, Marina; Finotti, Enrico
Abstract: The present study was performed to evaluate the distribution of phytochemicals in wheat grains and millstreams and the contribution of these compounds to the antioxidant activity. Bioactive molecules, although related to genotype, were highly affected by the milling procedure applied. Carotenoids were unevenly distributed in the kernel and lutein resulted to be the main carotenoid in all samples considered. The WSB method was confirmed to be a useful tool to detect yellow color intensity of semolina but it was not suitable to get information on the true content of carotenoids of the sample. Water-methanol soluble components showed antioxidant activity which decreased from the outer to the inner parts of the kernel. Chloroform-methanol soluble compounds showed generally negligible or negative antioxidant activity due to the inadequate amount of antioxidants unable to counteract oxidative processes already in progress.